Short-term maintenance on a high-sucrose diet alleviates aging-induced sleep fragmentation in drosophila - Sang Hyuk Lee (Taylor & Francis Group, 2021)
Sleep is a fundamental behavior in an animal’s life influenced by many internal and external factors, such as aging and diet. Critically, poor sleep quality places people at risk of serious medical conditions. Because aging impairs quality of sleep, measures to improve sleep quality for elderly people are needed. Given that diet can influence many aspects of sleep, we investigated whether a high-sucrose diet (HSD) affected aging-induced sleep fragmentation using the fruit fly, Drosophila melanogaster. Drosophila is a valuable model for studying sleep due to its genetic tractability and many similarities with mammalian sleep. Total sleep duration, sleep bout numbers (SBN), and average sleep bout length (ABL) were compared between young and old flies on a normal sucrose diet (NSD) or HSD. On the NSD, old flies slept slightly more and showed increased SBN and reduced ABL, indicating increased sleep fragmentation. Short-term maintenance of flies in HSD (up to 8 days), but not long-term maintenance (up to 35 days), suppressed aging-induced sleep fragmentation. Our study provides meaningful strategies for preventing the deterioration of sleep quality in the elderly.